A PRAGMATIC ANALYSIS OF FLOUTING MAXIM FOUND IN FRIENDS MOVIE - Wida Monalisa Purba; Putu Nur Ayomi (IKIP Siliwangi, 2022)
This article focuses on finding the types of flouting maxim in the Friends film by all characters, especially in season 1, episodes 1-10. This research aims to find the types of flouting maxim and the reasons behind the characters flouted the maxim based on the context of the situation. This topic is part of pragmatics which studies whether humans as social beings who always interact can be cooperative and able to make the appropriate contribution as expected with the aim of creating quality communication, in accordance with the portion, relevant, and assuredly clear. The data were analyzed using the theory of Grice (1975) in classifying the types of flouting maxims that appear in the film and the analysis will be supported with the context of situation theory by Halliday (1985). This article uses qualitative methods and data collection using the observation method. Then as a result, 49 data flouting the maxim were identified in this movie. The data found represent all types of flouting maxim (Grice). However, the type of flouting maxim that most found is flouting maxim of relation. Keywords: Flouting Maxim, Cooperative Principle, Pragmatic, Movie